2001
DOI: 10.1562/0031-8655(2001)073<0297:eofroc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluence Rate on Cell Survival and Photobleaching in Meta-Tetra-(hydroxyphenyl)chlorin–photosensitized Colo 26 Multicell Tumor Spheroids¶

Abstract: We report the influence of fluence rate on the photobleaching and cell survival in Colo 26 multicell spheroids photosensitized by meta-tetra-(hydroxyphenyl)chlorin (mTHPC). Photosensitizer degradation and therapeutic efficacy increased dramatically and progressively when the fluence rate was reduced over the range from 90 to 5 mW cm-2. These experimental results were compared to a mathematical model of photobleaching based on self-sensitized singlet oxygen reactions with the photosensitizer ground state. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 26 publications
14
57
0
Order By: Relevance
“…Since the oxygen supply is one of the limiting factors in PDT, this phenomenon could result from a too high initial oxygen consumption imposed by a high irradiance. This hypothesis is in agreement with the data and calculations of Foster's group [31,32].…”
Section: Photobleaching Monitoring and Ros Reporter Systemsupporting
confidence: 91%
“…Since the oxygen supply is one of the limiting factors in PDT, this phenomenon could result from a too high initial oxygen consumption imposed by a high irradiance. This hypothesis is in agreement with the data and calculations of Foster's group [31,32].…”
Section: Photobleaching Monitoring and Ros Reporter Systemsupporting
confidence: 91%
“…They showed that, for a given total light°uence, both the 1 O 2 counts and the tumor response decreased as the°uence rate increased (from 30 to 120 mWcm À1 using an interstitial diffusing¯ber to deliver the light). This reduction in PDT e±cacy at high light°uence rates has been reported also in vitro 19 and in vivo 20 and is well understood in terms of photochemical depletion of ground-state molecular oxygen. 21 A particular advantage of the luminescence instrument used by Yamamoto et al 13 was the ability to collect the luminescence emitted from the tumor by a¯ber optic bundle.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies from our group have demonstrated that BPD-PDT significantly decreases the size of 3-D OvCa nodules 20 and synergistically enhances carboplatin efficacy. 21 These and other studies 31,59,61,68 suggest a role for 3-D models in improved treatment planning, including for PDT regimens. The myriad of variables that influence PDT outcomes, including the marginal benefit gained from dose escalation, PS concentration, fluence, and the metrics used to evaluate treatment response require further optimization.…”
Section: Introductionmentioning
confidence: 85%